Proposal to improve partnerships between the private sector and Federal University of Triângulo Mineiro - Luciana da Costa e Silva Martins; Geraldo José Carneiro Neto; Douglas Moura Miranda; Deusmaque Carneiro Ferreira (Revista Gestão Universitária na América Latina)
The aim of the current study is to investigate difficulties in establishing Research, Development and Innovation (RD&I) partnerships between the private sector and Federal University of Triângulo Mineiro (UFTM). Initially, the current process of RD&I partnership agreements with the Technological Innovation Center (TIC) was mapped and two questionnaires were applied, respectively, to researchers at the university and to private sector companies operating in Uberaba City-MG. Results have evidenced that participants presented medium-to-poor level of knowledge about incentives to university-company interactions provided for the legislation through the Legal Framework for Science, Technology and Innovation. In addition, 55.9% of the investigated companies were interested in developing RD&I projects in partnership with the aforementioned university, whereas 44.1% of them were not. With respect to factors making it hard to establish partnerships, participants have mentioned poor knowledge about procedures and excessive bureaucracy. The greater their relationship with the university, the more bureaucracy was perceived by them. Finally, improvements were suggested to encourage partnerships at the university and to develop procedures for both proposing and formalizing partnership agreements between the private sector and UFTM.